Extended High Frequency Hearing, but Not Tinnitus, Is Associated With Every-Day Cognitive Performance - Waechter, Sebastian; Wilson, Wayne J.; Magnusson, Måns; Brännström, K. Jonas (Frontiers in Psychology, 2022)
Research into the potential associations between tinnitus and cognition has investigated specific cognitive domains in laboratory settings despite adults with tinnitus reporting broad cognitive difficulties in every-day life. To address this limitation, the present study compared performance and perceived exertion on a visual office-like task in 38 adults with tinnitus (19 with normal hearing and 19 with hearing loss) and 38 adults without tinnitus (19 with normal hearing and 19 with hearing loss) matched for age, sex and educational background. All participants were also assessed for hearing, anxiety and depression, and participants with tinnitus were also assessed for tinnitus handicap. No associations were found between presence of tinnitus and cognitive performance (mean total rate correct score on the visual office-like task being 2.9 for the tinnitus group, 2.8 for the control group, p = 0.612) and perceived exertion (mean ratings of perceived exertion on the Borg CR10-scale being 5.8 for the tinnitus group, 6.5 for the control group, p = 0.063) on the visual office-like task when corrected for standard (0.125 to 8 kHz) and extended high frequency (10 to 16 kHz) hearing thresholds, anxiety, and depression. The correction for extended high frequency average (10, 12.5, 14, and 16 kHz) hearing threshold was significant for performance (p = 0.009) but not perceived exertion on the visual office-like task. Overall, the results showed extended high frequency hearing, but not tinnitus, was associated with every-day cognitive performance. This indicates clinical testing of hearing thresholds above 8 kHz could support clinicians’ identification and management of cognitive difficulties. One management method suggested by the current findings would include provision of auditory stimulation at frequencies exceeding the frequency response of many current hearing aids.